PEMANFAATAN LIMBAH PERTANIAN UNTUK MENDUKUNG PENINGKATAN KUALITAS LAHAN DAN PRODUKTIVITAS PADI SAWAH - Sri Karyaningsih (BUANA SAINS, 2012)
Food demand especially rice is increased similary with populations of people and rice self sufficient program of the indonesian goverment. On the other hand rice production systems was risk due to decreases of quality and quantity agriculture land, climate change and increased pest and diseases infestations. One of new approach and technology to added value and efficiency of farming is by using agriculture biomass for organic fertilizer. Field experiment was conducted at Tegalsari village, Weru Subdistrict and Sukoharjo District during November 2009 to July 2010. The result showed that rice productivity range from 5,65 to 6,80 t/ha with avarage 6,26 t/ha. Organic fertilizer increased rice production by 17,20%, and C-organic soil content 0,30. Agriculture biomass potentially reduced applications of anorganic fertilizer by 54 kg Urea, 89 kg SP36 and 60 kg KCL per ha/year